High-temperature thermal discharge inhibits plankton community metabolism in a partly eutrophicated bay in China - Liu, Huaxue; Li, Jiajun; Wang, Huijuan; Huang, Honghui; Xie, Fuwu; Song, Xingyu (Frontiers in Marine Science, 2023)
Managing the marine ecosystem effectively requires studying the response of plankton community metabolism to warming. Moreover, warming caused by thermal discharge is known to significantly raise the water temperatures in the nuclear power plants. However, effects of thermal discharge on planktonic community metabolic characteristics, especially net community production, in surrounding waters remain poorly understood. Therefore, in this study, we aimed to analyze the characteristics of plankton community metabolism in thermal discharge area of the Daya Bay, China. The investigations were conducted in August 2016 and January 2017. Our results showed that the plankton community metabolism was promoted in moderately warm regions (29.4-30 °C), with higher gross primary production and community respiration than in high- and extremely high-temperature regions; meanwhile, plankton community metabolism was evidently inhibited in high (31.4 °C in winter) or extremely high (36°C in summer) temperature regions, thereby exhibiting heterotrophic metabolism state. Our findings indicate that warming could affect plankton community carbon metabolism in the Daya Bay, thereby declining the stability of the marine ecosystem.